Communication Strategies By The Leaders Of Pt. Enseval Putra Megatrading, Tbk Bengkulu - Herdiansyah, Reski; Putra , Dilmai; Dianthi , Martha Heriniazwi (Universitas Dehasen Bengkulu, 2026)
The strategy of communication by leadership is one of the important factors in creating a conducive work environment and enhancing employee motivation. This research is motivated by the significance of the role of leadership in delivering information and building healthy interpersonal relationships in the workplace. The problem formulation in this study is how the communication strategy of PT. Enseval Putra Megatrading, Tbk Bengkulu motivates employees. The objective of this research is to describe the communication strategies implemented by company leaders to encourage employee spirit and performance. This research uses a qualitative descriptive approach. Data collection techniques were conducted through in-depth interviews, direct observation, and documentation study. The research informants consisted of leaders, secretaries, warehouse heads, and staff employees. Data analysis used the interactive model by Miles and Huberman, through stages of data reduction, data presentation, and conclusion drawing. This study refers to Harold D. Lasswell's communication theory, which analyzes the communication process through five main elements: Who (who is the communicator), Says What (what is the message), In Which Channel (communication channel), To Whom (who is the communicator), and With What Effect (the effect of communication produced). The results of the study indicate that the leaders of PT. Enseval Bengkulu implement five communication strategies, namely information openness, two-way communication, personal approach, appreciation, and inspirational delivery of vision and mission. These strategies have proven to enhance employee motivation, engagement, and performance. Strategic leadership communication contributes positively to work spirit and productivity. The recommendation from this study is for leaders to continue developing more adaptive, responsive, and participatory communication, as well as to optimally utilize communication technology to reach all employees evenly.